Daily Share Price-changes for Eleven D-J Companies over Five Three-month Periods and Short-term Profit-seeking - John M. Hartwick (Queen's University, Department of Economics, 2017)
We link daily price-changes for 11 Dow-Jones companies for 5 three month periods to the prevailing interest rate. In "normal times", the interest carrying cost of owning a share exceeds average price change. In periods of high volatility (eg. August to November, 2008), average price change exceeds the interest carrying cost. We also observe considerable regularity across companies of volumes of shares traded per day and percentage price changes. The intercept differs across time periods (1995, 2006, 2007, 2008, 2010). Larger volumes yield larger price changes, on average.
Keywords: G10; G12; 330; interest carrying-cost; average share price changes